Pelatihan Peningkatan Keterampilan Literasi Digital Guru SMP: Strategi Mempersiapkan Siswa Menghadapi Tantangan Teknologi - Ningrum Astriawati; Gino Erman Agusta; Haryani; Ardystia Maha Sari; Abdurahman Milad (Universitas Veteran Bangun Nusantara, 2025)
The use of Artificial Intelligence (AI) in education opened up significant opportunities to improve the quality of learning through personalization, efficiency, and innovation. This community service program aimed to enhance the digital literacy of junior high school teachers at SMP IT Baitussalam Prambanan, Yogyakarta by utilizing AI in the learning process. The program involved 14 teachers and included training on integrating AI into lesson planning, implementation, and evaluation using applications such as ChatGPT, Moodle, and coding tools. The methods employed included identifying teachers’ needs, preparing training materials, conducting activities, and evaluating the impact. The training results showed an increase in teachers’ confidence in developing AI-based Lesson Plans (RPP) and using interactive learning media. AI also helped teachers better understand students’ learning needs, creating a more personalized and effective learning experience. The program concluded that AI-based training had a significant positive impact in supporting the transformation of learning, with recommendations for follow-up training to deepen teachers' understanding of AI technology in broader educational contexts.